Implications of the 3-to-2 Merger on Telecommunication Service Prices: Case Study of Thailand - Chate Khemakongkanonth; Pratompong Srinuan (International Telecommunications Society (ITS), 2023)
In the past decades, Thailand's telecommunication market has accommodated 3 dominant providers ranked by subscribers, namely AIS, TRUE, and DTAC, along with one minor government-owned provider NT. In 2021, TRUE and DTAC requested to merge, which was eventually approved by the national regulatory agency in 2022. The 3-to-2 merger here is likely to be more impactful onto the market than more typically seen 4-to-3 mergers. This paper estimates post-merger changes in prices and whether possible efficiency gained due to the merger would be sufficient to deter the mergers from raising their prices. By using time series data on pre-paid and post-paid subscribers of the major three operators, a merger simulation was employed. The proxy for price used in the simulation was average revenue per user divided by minute of use. The simulation assumed that collusion levels between the 3 operators before and after the merger mirror HHIs, and set the level of efficiency gain at 10%. The result showed a 12.95% increase in market price on average. Upward pricing pressure, under a similar setup, indicated a 7.19% increase in average market price. The result justified retail tariff regulation to limit the negative impact on consumers.
Keywords: 330; Mobile telecommunications; Merger simulation; Upward pricing pressure; Demand estimation; Thailand